Hospitalization among Individuals Waitlisted for Kidney Transplant - Newman, Kira L (Transplantation, 2017)
BACKGROUND: For patients waitlisted for a deceased-donor kidney, hospitalization is associated with a lower likelihood of transplantation and worse posttransplant outcomes. However, individual-, neighborhood-, and regional-level risk factors for hospitalization throughout the waitlist period and specific causes of hospitalization in this population are unknown. METHODS: We used United States Renal Data System Medicare-linked data on patients waitlisted between 2005 and 2013 with continuous enrollment in Medicare Parts A & B (n=53 810) to examine the association between annual hospitalization rate and a variety of demographic, clinical, and social factors. We used multi-level multivariable ordinal logistic regression to estimate odds ratios (OR). RESULTS: Factors associated with significantly increased hospitalization rates among waitlisted individuals included older age, female sex, more years on dialysis prior to waitlisting, tobacco use, PRA>0, public insurance or no insurance at ESRD diagnosis, more regional acute care hospital beds, and urban residence (all p<0.05). Among patients’ dialysis-dependent when waitlisted, individuals with arteriovenous fistulas were significantly less likely than individuals with indwelling catheters or grafts to be hospitalized (OR=0.79 and 0.82, respectively, both p<0.001). The most common causes of hospitalization were complications related to devices, implants, and grafts; hypertension; and sepsis. CONCLUSION: Individual- and regional-level variables were significantly associated with hospitalization while waitlisted, suggesting that personal, health-system, and geographic factors may impact patients’ risk. Conditions related to dialysis access and comorbidities were common hospitalization causes, underscoring the importance proper access management and care for additional chronic health conditions.